Growth and characterization of SiOx nanowires by VLS and SLS growth mechanism - Rho, D.-H.; Kim, J.-S.; Byun, D.-J.; Yang, J.-W.; Lee, J.-H.; Kim, N.-R. (Materials Research Society Symposium Proceedings, 2005)
SiOx nanowire were synthesized using VLS (vapor-liquid-solid) and SLS (ssolid-liquid-solid) growth mechanism. Grown nanowires had a different shapes by the kind of substrates and kind of catalysts. Diameters and lengths of grown nanowires were varied with growth conditions. By vapor evaporation method, used substrates effected growth scheme and density of nanowires because of differences of catalyst nucleation characteristics. Grown nanowires showed different microstructures and optical properties. By catalyst evaporation method, various shapes of SiOx nanowires were grown. These shapes of nanowire were formed by the typical reaction of catalyst and Si source. Measured optical properties show blue luminescence about 430nm because of oxygen defects in the nannowire. ？ 2005 Materials Research Society.